IMPLEMENTASI PENDEKATAN MULTIPLE INTELLIGENCES DALAM METODE PRAKTIKUM UNTUK MELIHAT PENINGKATAN KETERAMPILAN PROSES SAINS SISWA SMA (UPEJ Unnes Physics Education Journal, 2013)
Nowadays, learning which is needed not only on the evaluated orientation but also the process of learning itself. LearningÂ  model bases on the scientical process as the form of learning strategy, practically it requires the activities of all component such as students, teacher, and school. This research aims to know the improvement of students scientical process skill using the implementation of Multiple Intelligences approach on practicum methode. The experiment research designs Posttest Control Group Design Only is held in senior high school 2 of Magelang. The subjects are seconds semester of X graders 2012/2013. The technic of data analysis which is used is Gain test and T test. Based on the result of data analysis can be concluded that the scientical process improvement of experimental group which using Multiple Intelligences approach on practicum methode is higher than the control group which applies the random distribution